Globalization and Electoral Outcomes: Evidence from Italy - Mauro Caselli; Andrea Fracasso; Silvio Traverso (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
We study whether and to what extent the electoral dynamics in Italy over the 1994-2008 period can be explained by the development of economic factors associated with globalization. To measure the level of exposure to globalization for local labor markets, our main unit of analysis, we use the intensity of import competition from China and the presence of immigrants. Looking at parties' political positions and employing an estimation strategy that accounts for endogeneity and time-invariant unobserved effects across local labor markets, we find that both immigration intensity and exposure to import competition from China have contributed positively to the electoral outcomes of far-right parties, whereas only the former has produced a positive effect on the votes of right-wing and traditionalist/authoritarian/nationalist parties. On the other hand, neither of them has had an effect on far-left parties. Moreover, electoral turnout has responded negatively to an increased presence of migrants. While the above effects seem to work through the mediation of labor markets, the results suggest that other mechanisms at the level of local communities are also at play.
Keywords: 330